Lumbar Disc Herniations in Children. A Five-Year Single Center Experience - Horatiu Alexandru MOISA; Dan Aurel NICA; Maria Alexandra ANDREI; Ramona Manuela SAVU (Modern Medicine)
Lumbar disc herniations represent one of the most common complications of degenerative disc disease in adults and have a favorable outcome with surgery. In children, on the other hand, disc prolapse is a relatively rare pathologic entity mandating cautious multimodal management. This paper presents the five-year long experience of a single pediatric neurosurgical unit and our management strategy for children diagnosed with lumbar disc prolapse.